Effect of intracerebroventricular injection of ramipril on the drinking response caused by injection of noradrenaline into the third ventricle - Barros, V. M. [UNESP]; Saad, W. A. [UNESP]; Camargo, L. A.A. [UNESP]; Renzi, A. [UNESP]; Menani, J. V. [UNESP] (My University, 1996)
We studied the effect of ramipril injected into the third ventricle (3rdV) on the control of water intake induced by injection of noradrenaline into the 3rdV of adult male Holtzman rats (250-300 g) implanted with a chronic stainless steel cannula into the 3rdV. The injection volume was always 1 μl and was injected over a period of 30-60 sec. Control animals were injected with 0.15 M NaCl. After the injection of isotonic saline (control, 0.15 M NaCl) into the 3rdV, water ingestion was 0.3 ± 0.1 ml/h. Ramipril (1 μg/μl) injected into the 3rdV prior to isotonic saline produced no changes in water ingestion (0.4 ± 0.2 ml/h). The injection of noradrenaline (40 nmol/μl) after isotonic saline induced an increase in water intake (3.0 ± 1.1 ml/h). The prior injection of ramipril decreased this ingestion to 1.8 ± 0.3 ml/h. These data show that the inhibition of converting enzyme in the brain reduces the water intake induced by catecholaminergic stimulation. We conclude that the brain is able to transform the prodrug ramipril into the active drug ramiprilat.
Keywords: converting-enzyme inhibitor; noradrenaline; ramipril; water ingestion